Calomys tener (Winge, 1887) (Rodentia: Cricetidae: Sigmodontinae): Filling gaps - Fernando Quintela; Everton da Silveira; Diana Dellagnese; Cristina Cademartori (Check List, 2014)
Calomys tener is a widely distributed species in Brazil. Herein we report the second record of C. tener in state of Rio Grande do Sul about 80 km northwestwards from the previous southernmost known limit in Brazil.